BIOREMEDIASI LIMBAH CAIR INDUSTRI TAHU MENGGUNAKAN EFEKTIF MIKROORGANISME (EM4) - Jasmiyati Jasmiyati; Sofia Anita; Thamrin Thamrin (Program Pascasarjana Universitas Riau, 2010)
The experiment was conducted to in order know the effect of effective microorganisms(EM4) on the tofu waste water in the Chemical laboratory FMIPA Riau University Pekanbaruon 18 March - 08 April 2010. Samples were taken from outlet of tofu industry Sido RukunStreet Kecamatan Payung Sekaki. The treatment was using EM4 with concentration of 1:20(Treatment A), the second treatment was using concentration of EM4 1:10 (Treatment B) andC as control. The results of the experimental showed that Treatment A was more effectivethan Treatment B and Control in decreasing BOD and COD for 13 days experiment.